Assessment of airborne microorganisms in a craft brewery - Miller, Amanda Leah, author; Bunning, Marisa, advisor; Stone, Martha, committee member; Hyatt, Doreene, committee member (Colorado State University. Libraries, 2011)
Although pathogenic bacteria have little chance of surviving in beer due to its intrinsic antimicrobial hurdles, there are other microorganisms capable of surviving and spoiling beer. The quality of all food products including beer are not only affected by the integrity of the raw materials, and cleanliness of the equipment and packaging materials, but also by the purity of the environmental air surrounding the processing area. The purpose of this project was to examine the environmental microbial air quality within various areas of a craft brewery with special emphasis on potential beer spoiling bacteria. First, samples inside the brewery and samples outside the brewery were collected to establish a baseline of data, identify areas of concern, and to examine the effect of seasonality. Those areas of concern then were sampled more often and also were sampled based on the risk of product contamination. The canning line within the brewery was identified as a specific area of concern. Bottling and canning lines in breweries often are considered non-closed production equipment and have the ability to become contaminated from outside sources including the environment. The air was sampled 307 times over a period of 22 months using an automated impaction sieve sampler pulling 80 liters of air. Samples were plated both aerobically and anaerobically. The aerobic plates were used for a general cleanliness of the area while the anaerobic plates were included to examine for beer spoiling organisms. The standard (specification limit) used for the indication of a contaminated area was a plate with 40 colony forming units (CFU) or more per 80 liters of air sampled. The results of this study revealed that testing for airborne microorganisms is highly recommended in the craft brewing industry due to the potential for the impurity of the environmental air surrounding the processing area. Seasonality had an effect on total number of aerobic airborne microorganisms with the spring months being approximately five times higher than other months. The canning line in the brewery was found to be contaminated with beer spoiling bacteria on average 75% of the time. Critical areas in the brewery, such as the bottling and canning lines, should be routinely tested for airborne microorganisms as they could lead to final product contamination. Routine microbial environmental air testing is a good indicator of overall brewery cleanliness.
Keywords: airborne bacteria; craft brewery; beer spoiling bacteria; beer; airborne microorganisms